Students' experiences of academic play within transitional space in higher education - Mackenzie, Helen Elizabeth (2011)
This thesis argues that Donald Winnicott's theory of transitional space and play casts new light upon the ontological dimensions of students' experiences of transition within Higher Education. Winnicott enables the illumination of the different ways that students might react, cope and personally develop when faced with similarity, difference and change, demonstrating this can have powerful influences upon the facilitation and hindrance of individuals’ transitions.